P53 gene alterations and protein accumulation in colorectal cancer. Issue 2 (April 1996) - Bertorelle, R; Esposito, G; Belluco, C; Bonaldi, L; Del Mistro, A; Nitti, D; Lise, M; Chieco-Bianchi, L
Abstract : Aim —To correlate immunohistochemical staining with single strand conformation polymorphism (SSCP) analysis of the p53 gene in colorectal cancer in order to understand how the findings provided by the two techniques complement each other in defining p53 functional status. Methods —Frozen tumour tissue from 94 patients with colorectal cancer was studied for p53 protein accumulation and gene mutations. Accumulation of p53 protein was detected by immunohistochemistry using PAb1801 and BP53-12-1 monoclonal antibodies. The findings were then compared with SSCP analysis of exons 5 to 8 of the p53 gene. All cases with a positive result by SSCP analysis were confirmed by sequencing. Results —Nuclear staining was observed in 51 (54.2%) cases. SSCP analysis of the DNA amplified by PCR revealed that the electrophoretic pattern had shifted in 30 cases; sequence analysis confirmed the occurrence of a mutation in 29 cases and of a polymorphism in one. In 27 cases both assays gave a positive result, and in 40 both were negative; therefore, concordance between PCR-SSCP and immunohistochemistry was seen in 72% of cases. Conclusion —The data indicate that positive immunostaining corresponds with the presence of a mutation in most, but not all, cases studied; other mechanisms could be responsible for stabilisation and accumulation of p53 protein in the nucleus. Nonsense mutations which do not confer stability on the protein will not be detected by immunohistochemistry and false negative results can also occur with SSCP analysis.